Experimental shear testing of small-scale corrugated web girders used in conventional buildings. (February 2022) - Deng, Hao; Shao, Yong-Bo; Hassanein, M.F.
Abstract: The shear strength of steel corrugated web girders (SCWGs) has been widely investigated due to their excellent mechanical behaviour. However, experiments of SCWGs especially those of the small-scale that are used in conventional buildings are limited. Three full-scale shear capacity experiments are performed for SCWGs with different web heights and thicknesses. The developments of the strains in some critical sections and the load-deflection curves for the three specimens are measured and analysed. ABAQUS software, the worldwide finite element (FE) commercial programme, is then used to simulate the shear behaviour of SCWGs by considering the height and thickness of the webs, fold widths and corrugation angles. The available design strengths are collected and compared with the experimentally and numerically obtained strengths. The recommended design models for the different cases of SCWGs used in conventional steel buildings are then assigned. Generally, the method of Hassanein and Kharoob (2013) can best predict the strengths of SCWGs with the same fold widths, while that of Moon et al. (2009) best predicts the shear strengths of those of different fold widths. Additionally, the discussions show that the efficient shear design of SCWGs can be reached by increasing the thickness of the corrugated web, not through increasing the web height, length of flat folds and/or corrugation angles, when considering balancing factors between the weight and shear strength of webs. Finally, behavioural characteristics that enhance the design of the current girders are outlined. Graphical abstract: Unlabelled Image Highlights: Three small-scale SCWGs have been tested. The distribution of web shear and available design equations have been examined. FE simulations have been done to analyze the effect of fold widths. The weight of CWs have been quantified with respect to the girders' strengths.